DEVELOPMENT OF EDUCATIONAL GAME-BASED MATH LEARNING MEDIA ORIENTED TO THE NUMERACY SKILLS OF GRADE VIII STUDENTS - Hakim, Nur Akmalul; Setyaningrum, Wahyu (Universitas Negeri Yogyakarta, 2025)
This research aims to develop educational game-based learning media on chance material that is oriented towards students' numeracy skills. The development model used in this research is the ADDIE development model. The sampling technique in this study used cluster sampling technique. The research instruments consisted of media validation sheets for material experts and media experts, teacher assessment sheets, student response questionnaires, learning implementation observation sheets, and numeracy tests. The results of the analysis, in terms of validity, showed that the educational game-based learning media met the excellent criteria in the aspects of content quality, instructional quality, and technical quality with the acquisition of an average score from material experts and media experts which amounted to 4.38 from a maximum score of 5. In terms of practicality, the learning media is considered good with an average score of teacher assessment sheet of 4.09 from a maximum score of 5, an average score of student response questionnaire of 3.45 from a maximum score of 4, and a percentage of learning implementation of 94.4%. In terms of effectiveness, the learning media is considered effective because 83.52% of students experience an increase in numeracy skills after using the learning media.